High Responsivity β-Ga2O3 Metal-Semiconductor-Metal Solar-Blind Photodetectors with Ultraviolet Transparent Graphene Electrodes - Oh, Sooyeoun; Kim, Chang Koo; Kim, Jihyun (ACS Photonics, 2018)
We demonstrated high responsivity metal-semiconductor-metal (MSM) solar-blind photodetectors by integrating exfoliated β-Ga2O3 microlayers with graphene, which is a deep ultraviolet (UV) transparent and conductive electrode. Photodetectors with MSM structures commonly suffer from low responsivity, although they feature a facile fabrication process, low dark current, and fast response speed. The β-Ga2O3 MSM solar-blind photodetectors with graphene electrodes exhibited excellent operating characteristics including higher responsivity (∼29.8 A/W), photo-to-dark current ratio (∼1 × 106%), rejection ratio (R254nm/R365nm, ∼9.4 × 103), detectivity (∼1 × 1012 Jones), and operating speed to UV-C wavelengths, compared with MSM photodetectors with conventional metal electrodes. Absence of shading by the integration of graphene with β-Ga2O3 allows maximum exposure to the incident photons, suggesting a great potential for deep UV optoelectronic applications.
Keywords: Conductive electrodes; Conventional metals; Gallium oxides; Metal semiconductor metal; Operating characteristics; Solar blind; Solar-blind photodetectors; Transparent graphene; Gallium oxide; graphene; photodetectors; solar-blind